Conversational flow and entitativity: The role of status. (22nd February 2013) - Koudenburg, Namkje; Postmes, Tom; Gordijn, Ernestine H.
<x xml:space="preserve">Abstract</x> This study examines the process by which perceptions of conversational flow foster an emergent sense of group entitativity. We propose that conversational flow influences more than just the quality of interpersonal relations: it signals entitativity – social unity at the group level. We predicted that when conversations are intermitted by brief silences after a target has spoken, this is perceived as disruptive for targets of low social status within the group: For low‐status group members, such pauses raise concerns over respect and inclusion. However, for high‐status group members, a similar intermission may be interpreted as an acknowledgement of their distinctive position in the group, and may therefore bolster the hierarchy and unity of the group. Two experiments support these hypotheses. Study 1 (N = 77) manipulated status in conversations of a target participant with confederates. Study 2 (N = 138) replicates the effect among participants who watch a videotaped conversation. Both studies show the predicted pattern, and suggest that belonging (Study 1) and perceived respect (Study 2) may mediate effects of condition on perceptions of group entitativity.